Indigenous yeast can increase the phenolic acid and volatile ester compounds in Petit Manseng wine - Wang, Yanyu; Wang, Miao; Li, Wenjuan; Wang, Xinyuan; Kong, Weifu; Huang, Weidong; Zhan, Jicheng; Xia, Guangli; You, Yilin (Frontiers in Nutrition, 2022)
Indigenous yeasts are generally found in grapes, vineyards, and natural environments. Sequential inoculation and fermentation with non-Saccharomyces cerevisiae yeast (H30) and Saccharomyces cerevisiae (YT13) also improve the flavor of wine. This study sequentially inoculated fermented Petit Manseng and natural grape juice with native H30 and YT13 selected from vineyards in Yantai, China. The sensory characteristics of Petit Manseng wine were evaluated by detecting the primary organic acids, phenolic acid compounds, and volatile ester compounds. The results showed that the lactic acid content of the natural wine fermented sequentially with H30 and YT13 increased by 490 μg/L compared with the control group, while the ferulic acid content was 1.4 times that of the single-yeast fermentation group. Furthermore, butyrolactone and anthocyanidin propionate were present in the mixed fermentation group, increasing the aroma complexity of Petit Manseng wine and providing high-quality yeast resources that increase the regional characteristics when producing dry white wine.